Designing a gingerbread product based on gluten-free vegetable compositions - G. E. Rysmukhambetova; K. E. Beloglazova; Yu. V. Ushakova; I. V. Ziruk (Новые технологии, 2023)
The research is devoted to the creation of a new recipe and technological solutions for the production of gluten-free gingerbread products for people who need dietary nutrition. Our studies were carried out in accordance with GOST 15810-2014 «Confectionery products. Gingerbread products. General specifications». Based on marketing research, it has been established that nowadays production of gluten-free confectionery products, including gingerbread ones, is underdeveloped in the region. The following samples of gingerbread products are considered in the research: the control one – 100% wheat flour; No. 1 – 50% rice and 50% corn flour; No. 2 – 50% corn and 50% pumpkin flour. As a result of the experiments, sample No. 1 with the best organoleptic characteristics has been selected. The gluten level in the gingerbread product under study was calculated, and it amounted to 7 mg/kg, which according to TR CU 027/2012 was lower than the normalized value (20 mg/kg). Therefore, this product belongs to the «gluten free» product group. It has been established that due to the high water absorption capacity, the introduction of mixture No. 1 into the food industry is relevant, since there is a greater rise in the dough during baking and less thickening of starch grains. As a result of our calculations of the chemical composition of this product, it has been found that through the use of an alternative type of raw material, it is possible to design products with various contents of food and biologically active substances, including a vitamin–mineral complex, which are not inferior in their characteristics to traditional products made from wheat flour. Thus, the studies conducted have shown that the use of non-traditional types of raw materials (rice and corn flour) allows one to make gluten-free products with high quality indicators, including organoleptic, structural-mechanical properties and enriched in nutritional value.